Climate Change and Vulnerability of the Arctic Elderly: An Assessment from Human Rights Point of View - Shahnaj Begum (CES Working Papers, 2012)
There are increasing challenges among the elderly in the Arctic region. Global warming due to climate change is one of the major reasons for these challenges. Because of climate change temperature in the region increases, which results in rapid melting of sea ice causing various environmental, social, cultural and economic problems. Population in the region suffers from these problems where elderly people are the most vulnerable. Climate change has already affected the elderly lives in different ways, such as, by physical, social, political, cultural and psychological ways. These have serious consequences in terms of human rights of this vulnerable group of people. However, the elderly people's human rights issues have not been adequately researched in the context of this region. The goal of this paper is to present elderly related human rights issues, particularly the rights that are affected due to climate change in this specific region.
Keywords: Q5; R11; 330; elderly; Challenges; climate change; human rights; Arctic region; vulnerable Romania